Long-term follow-up of surgical treatment of thyroid-associated orbitopathy restrictive strabismus - Savino, Gustavo; Mattei, Roberta; Salerni, Annabella; Fossataro, Claudia; Pafundi, Pia Clara (Frontiers in Endocrinology, 2022)
Objective: Thyroid associated orbitopathy (TAO) is the most frequent cause of extraocular muscle enlargement, with consecutive restrictive strabismus. Main involved muscles are inferior and medial rectus, resulting in horizontal esotropia and/or vertical strabismus. Surgery may either establish or improve binocular single vision. Aim of the present study is to describe long-term follow-up of patients who underwent horizontal or vertical TAO strabismus surgery. Methods. This observational retrospective study included 29 patients suffering either from vertical or horizontal TAO strabismus and diplopia, of whom 11 underwent bilateral medial recti muscle recession (Group A) and 18 to unilateral inferior rectus muscle recession (Group B). Endpoint of the study was the assessment of changes in deviation angle and diplopia across four timepoints (baseline, 7 days, 6 and 24 months) in each group. Results: In Group A, horizontal deviation angle significantly decreased 7 days after intervention (p<0.001), without modifications overtime. In Group B, both deviation angle in primary and down-gaze position significantly decreased from baseline, both 7 days after surgery (p<0.001) and at 6 months (p=0.040). An overcorrection, with an inversion of vertical deviation angle, was observed across the different timepoints. Conclusions: Horizontal TAO strabismus correction leads to significant improvements of deviation angle and diplopia, with a stable undercorrection overtime. Inferior rectus recession leads to more unstable results, with a trend towards overcorrection limited to the first 6 months after surgery.